Teaching english to young learners - Onea Mária (2004)
This thesis examines the importance of teaching reading in the language learning process. Throughout reading activities taken from Chatterbox 3 I will prove that teaching reading can be interesting and it is equally useful and worthy as the other skills and that the role of teacher is tremendous in making the lessons enjoyable and active. Through reading children can develop vocabulary, structures and pronounciation and can learn that reading is a joyful activity.